How university teachers’ digital literacy influences their innovative ability: a system dynamics theoretical modeling and simulation study - Mao, Zhangwei; Tong, Simiao; Jiang, Chao; Yan, Sijia; Bai, Yuntao (Frontiers in Psychology, 2026)
The global digital transformation is driving profound changes in modern education, with university teachers’ digital literacy and innovation capabilities gradually becoming key factors in advancing digital education reform and enhancing a nation’s international competitiveness and soft power. Adopting a dynamic perspective, this study abstractly constructs a system dynamics model spanning from the digital ecosystem layer to the psychological capital layer and ultimately to the innovation output layer. By incorporating simulation data, the study integrates teachers’ digital literacy, psychological factors, and innovation capabilities into the simulation system to examine the impact of digital literacy on teachers’ innovation capacity and reveal its underlying mechanisms. The findings indicate that university teachers’ digital literacy strengthens along the dynamic pathway of “psychological capital accumulation—self-efficacy enhancement—well-being improvement—cognitive closure reduction.” Psychological factors such as teachers’ self-efficacy, flow experience intensity, and well-being play significant mediating roles, while institutional technical support further reinforces this pathway. Notably, when digital technology complexity reaches extremely high levels, teachers’ flow experience intensity drops to its lowest point around the 0.5-period mark, exhibiting a “U”-shaped curve. On one hand, this study addresses gaps in existing research by analyzing the dynamic mechanisms through which teachers’ digital literacy influences innovation capabilities, overcoming the limitations of traditional static theories. On the other hand, it strengthens the digital knowledge framework for teachers and deepens the practical application of dynamic systems theory in educational transformation.